(untitled) (Revista Torreón Universitario, 2015)
This investigation concerns the proper use of teaching and learning strategies in the implementation of a multimedia software in Mathematics and Language Arts subjects in fifth and sixth grade at Jose de la Cruz Mena primary school in Jinotepe-Carazo. According to the research characteristics it has a qualitative approach. The information was obtained through: key informants, observation and focus group, it is a descriptive and a cross-sectional study. The software was designed by students from the Facultad Regional Multidisciplinaria in Carazo, available resources to be installed and to be used in primary school, starting in the school object of study, and then, extend the project to primary schools from Jinotepe with ICT classrooms. It was found that teachers in study have some difficulties with the use of technology, such as, little knowledge of computers and internet, they have no e-mail and are therefore it is a disadvantage with their students. Teachers do not have a clear definition of teaching-learning strategies in the use of educational software so that the appropriate use of available resources is difficult. It is recommended to strengthen the teaching-learning process, methodological strategies that allow the development of competences must be facilitated to teachers in the use of ICTs when implementing the educative software.